2021
DOI: 10.1186/s12935-021-02200-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of lenvatinib monotreatment and lenvatinib-based combination therapy for patients with unresectable hepatocellular carcinoma: a retrospective, real-world study in China

Abstract: Background Lenvatinib and lenvatinib-based combination treatments are widely used in patients with unresectable hepatocellular carcinoma (uHCC) in clinical practice, but their curative effect and safety need further study in the real world. Methods This was a retrospective study involving patients with uHCC receiving lenvatinib monotherapy and lenvatinib-based combination treatment between Nov, 2018 and Sep, 2020 in Nanfang Hospital. Efficacy was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…This might be the cause of the result. In addition, compared with other studies in the literature, the PFS of lenvatinib-TACE was 5.5 -11.6 months (30)(31)(32), while the PFS of our LePD1-TACE triple treatment achieved 10.4 months, our results were in the upper range. Notably, the different results between these studies and our data should be viewed with caution.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…This might be the cause of the result. In addition, compared with other studies in the literature, the PFS of lenvatinib-TACE was 5.5 -11.6 months (30)(31)(32), while the PFS of our LePD1-TACE triple treatment achieved 10.4 months, our results were in the upper range. Notably, the different results between these studies and our data should be viewed with caution.…”
Section: Discussionsupporting
confidence: 49%
“…Secondly, our study was a singlearm design and was limited by the lack of a control group. Zhu et al (31) reported that the effectiveness of triple therapy (Lenvatinib + PD-1 inhibitors + TACE or HAIC) is not superior to dual therapy (Lenvatinib + PD-1 inhibitors or Lenvatinib + TACE or HAIC). Therefore, multicenter randomized controlled clinical trials need to be carried out to verify the efficacy and safety of different combinations.…”
Section: Discussionmentioning
confidence: 99%
“…It seemed that patients with advanced HCC might benefited from lenvatinib plus PD-1 blockades administration uniformly regardless of the majority baseline characteristic subgroups, which was basically consistent with a previous study initiated by Zhu et al that investigated the efficacy of lenvatinib monotherapy and lenvatinib-based combination therapy for patients with unresectable HCC. 31 The exploratory analysis demonstrated that almost all the baseline characteristic subgroups might benefit from lenvatinib and lenvatinib-based combination administration. These conclusions highlighted that the effectiveness of lenvatinib plus PD-1 blockades was stable and balanced.…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter analysis in Korea also confirmed that lenvatinib has a good curative effect on aHCC patients, and the treatment is well tolerated by patients [ 55 ]. Further studies have found that for patients with uHCC, lenvatinib-based combination therapy (lenvatinib plus PD-1 antibody plus transcatheter arterial chemoembolization (TACE) or hepatic arterial infusion with drug filtration (HAIF), lenvatinib plus PD-1 antibody, lenvatinib plus TACE or HAIF) is more effective than lenvatinib monotherapy [ 56 ]. When uHCC patients become resistant to lenvatinib, sorafenib as a second-line treatment may be effective and may not worsen the liver reserve [ 57 ].…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%